A Resource Building Virtual Care: Programme Improving Symptoms and Social Functioning Among Female and Male Rural Veterans. Issue 1 (1st January 2021) - Bauer, Ashley; Amspoker, Amber B.; Fletcher, Terri L.; Jackson, Christie; Jacobs, Adam; Hogan, Julianna; Shammet, Rayan; Speicher, Sarah; Lindsay, Jan A.; Cloitre, Marylène
ABSTRACT: Background : Veterans have higher rates of PTSD and depression compared to the general population and experience substantial functional impairment. Impairment in social functioning has been a significant concern among Veterans, particularly rural Veterans, who have limited access to mental health care and are at risk for social isolation. Objective : A mixed-method study was implemented to evaluate the feasibility and effectiveness of webSTAIR, a web-based skills training programmeme, paired with home-based telehealth sessions. It was hypothesized that the programme would lead not only to reductions in PTSD and depression but also to improvements in social functioning. Method : Participants were 80 trauma-exposed Veterans enrolled in rural-serving VHA facilities with clinically elevated symptoms of either PTSD or depression. The study directed substantial outreach efforts to rural women Veterans and those who have experienced military sexual trauma (MST). Results : Significant improvements were obtained with PTSD and depression symptoms as well as in social functioning, emotion regulation, and interpersonal problems at post-treatment and 3-month follow-up. Ratings of therapeutic alliance were high as were reports of overall satisfaction in the programme. There were no differences by gender or MST status in symptom outcomes or satisfaction. Conclusions : The results support the feasibility and effectiveness of this integrated telehealth web-based skills training programme for both male and female Veterans as well as for those with and without MST. The focus on resource building and improved functioning make this programme of particular interest. Further testing is warranted. Abstract : HIGHLIGHTS: An online skills intervention, webSTAIR, paired with home-based telehealth sessions delivered to rural Veterans was effective in improving not only symptoms of PTSD and depression but also social functioning, a critical part of trauma recovery.